Brak formy kanonicznej w świetle wyroku c. De Angelis z dnia 9 lipca 2009 roku - Dzierżon, Ginter (Ius Matrimoniale, 2012)
The presented study is a commentary on an unpublished sentence of Roman Rota c. De Angelis issued on 8 July 2009. In his commentary, the author pointed out that the divergence between the decision of the courts of first and second instance resulted on the one hand form different approaches to the value of Circular Letter of Pontifical Council for Legislative Texts published in 2006 and, on the other hand, from different interpretative options concerning the category of withdrawal from the Catholic Church community of its members by means of a legal act. According to the author, for these reasons the status of the faithful participating, in the pastoral life of Fraternity of St. Pius was understood differently by the judges of the French court of first instance and the judges of Roman Rota. As a result, the court of the first instance decided that the parties involved in the schismatic community were not obliged to retain the canonical form; in contrast, the other court, taking into account the internal intention of the decision mad by the parties, came to a conclusion that they did not withdraw from the Church und so they ought to enter into marriage in the legally established form.